Thiazide‐Type Diuretics: Ongoing Considerations on Mechanism of Action - Sica, Domenic A. (J Clin Hypertens (Greenwich), 2007)
Thiazide‐type diuretics have enjoyed a considerable success in the management of hypertension. These drugs have assumed a standard‐of‐care position in the minds of many health care providers; however, a number of questions remain unresolved in relation to their use. Such questions include issues of mechanism of action, comparability to loop‐diuretics in their actions, class‐effect, and the basis for their additivity with non‐diuretic antihypertensive medication classes. Understanding these issues is important to the effective use of these compounds.